A Metallofullertube of Ce2@C100 with a Carbon Nanotube Segment: Synthesis, Single‐Molecule Conductance and Supramolecular Assembly. Issue 15 (10th February 2022) - Li, Wang; Qu, Fayu; Liu, Linshan; Zhang, Zhuxia; Liang, Jiayi; Lu, Yuxi; Zhang, Jie; Wang, Lin; Wang, Chunru; Wang, Taishan
Abstract: Tubular fullerenes can be considered as end‐capped carbon nanotubes with accurate structure, which are promising nanocarbon materials for advanced single‐molecule electronic devices. Herein, we report the synthesis and characterization of a metallofullertube Ce2 @ D 5 (450)‐C100, which has a tubular C100 cage with a carbon nanotube segment and two fullerene end‐caps. As there are structure correlations between tubular Ce2 @ D 5 (450)‐C100 and spherical Ce2 @ Ih ‐C80, their structure–property relationship has been compared by means of experimental and theoretical methods. Notably, single‐molecule conductance measurement determined that the conductivity of Ce2 @ D 5 (450)‐C100 was up to eight times larger than that of Ce2 @ I h ‐C80 . Furthermore, supramolecular assembly of Ce2 @ D 5 (450)‐C100 and a [12]CPP nanohoop was investigated, and theoretical calculations revealed that metallofullertube Ce2 @ D 5 (450)‐C100 adopted a "standing" configuration in the cavity of [12]CPP. These results demonstrate the special nature of this kind of metallofullertube. Abstract : A metallofullertube Ce2 @ D 5 (450)‐C100 with a carbon nanotube segment and two fullerene end‐caps was synthesized and characterized. Notably, Ce2 @ D 5 (450)‐C100 shows high single‐molecule conductivity and unique supramolecular assembly.